Toxicological evaluation of three methods of applying Rhizophora mangle on Galba cubensis (Mollusca: Gastropoda: Lymnaeidae) - Rangel Ruiz, Luis Jose; Arévalo-de la Cruz, Juan Armando; González-González, Guillermo; Hernández-Ovando, Jose Ángel; Gamboa-Aguilar, Jaquelina; Valdez-Leal, Juan de Dios (Ecosistemas y Recursos Agropecuarios, 2016)
The molluscicidal ecacy of Rhizophora mangle on Galba cubensis was evaluated through three bioas-says: two using aqueous extracts, one raw method extract (RME) and the other infusion method extract (IME), and direct application of powder (DAP). A completely randomized experimental design with three treatments, a control and ve replicates was used. LD50 and LD90 were determined using Probit-Log software. RME was used at 500, 400, 333 and 289 g L−1 concentrations; IME at 50, 25, 12.5 and 6 g L−1 ; and DAP extract at 0.540, 0.270 and 0.135 g. IME residence time and toxicity at 50 g L